Dukungan Penafsiran Sufistik al-Qur’an terhadap Emotional Spiritual Quotient (ESQ) - Thoriqul Aziz; Ahmad Zainal Abidin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
In classical Sufistic interpretation, it was taught about how to cultivate one's heart. This is done so that a servant can interact directly with Him. While in the modern world today it is taught about the Emotional Spiritual Quotient (ESQ) which incidentally has the same basis in the management of